The Effectiveness of Using Hand-Out Teaching Materials in the Learning of Microeconomic Theory Courses in the Students of Economic Education FKIP of Riau University - Haryana, Gani (Proceedings of the UR International Conference on Educational Sciences, 2018)
The research aims to formulate the use of hand-out as teaching materials in the subject of Microeconomic Theory, creating âembryosâ which will be developed into reference books for Microeconomic Theory courses, knowing the effectiveness of using hand-outteaching materials in improving the learning outcomes of Microeconomic Theory courses at the FKIP University Economic Education Study Program. The results of this study indicate that the existence of hand-out makes the lacture process more passionate, hand-outs that are shared with students become teaching materials that can help student make it easier to understand the material, learning otcomes between those who use hand-outs and those who do not use there are differences in mean learning outcomes of 18,78 (intervals 0-100), the use of hand-outs as teaching materials has increased 34,78% learning outcomes in the subjects of Microeconomic Theory in student of the Economic Education Study Program FKIP University of Riau.